Chemical composition of protein concentrate prepared from Yellowfin tuna Thunnus albacares roe by cook-dried process. Issue 1 (December 2016) - Lee, Hyun; Park, Sung; Yoon, In; Lee, Gyoon-Woo; Kim, Yong; Kim, Jin-Soo; Heu, Min
Abstract Roe is the term used to describe fish eggs (oocytes) gathered in skeins and is one of the most valuable food products from fishery sources. Thus, means of processing are required to convert the underutilized yellowfin tuna roes (YTR) into more marketable and acceptable forms as protein concentrate. Roe protein concentrates (RPCs) were prepared by cooking condition (boil-dried concentrate, BDC and steam-dried concentrate, SDC, respectively) and un-cooking condition (freeze-dried concentrate, FDC) from yellowfin tuna roe. The yield of RPCs was in the range from 22.2 to 25.3 g/100 g of roe. RPCs contained protein (72.3–77.3 %), moisture (4.3–5.6 %), lipid (10.6–11.3 %) and ash (4.3–5.7 %) as the major constituents. The prominent amino acids of RPCs were aspartic acid, 8.7–9.2, glutamic acid, 13.1–13.2, and leucine, 8.5–8.6 g/100 g of protein. Major differences were not observed in each of the amino acid. K, S, Na, and P as minerals were the major elements in RPCs. No difference noted in sodium dodecyl sulfate polyacrylamide gel electrophoresis protein band (15–100 K) possibly representing partial hydrolysis of myosin. Therefore, RPCs from YTR could be use potential protein ingredient for human food and animal feeds.